Answer ক. ax-3-a2x2-9
=ax-3-a2x2-32
=ax-3-a2(x+3)(x-3)
=a(x+3)-a2(x-3)(x+3)
=ax+3a-a2(x-3)(x+3)
=ax+3a-a2x2-9
উত্তর: =ax+3a-a2x2-9
খ. 1y(x-y)-1x(x+y)
=x(x+y)-y(x-y)xy(x-y)(x+y)
=x2+xy-xy+y2xy(x-y)(x+y)
=x2+y2xy(x-y)(x+y)
=x2+y2xy(x2-y2)
উত্তর: =x2+y2xy(x2-y2)
গ. x+11+x+x2-x-11-x+x2
=(x+1)(1-x+x2)-(x-1)(1+x+x2)(1+x+x2)(1-x+x2)
=(x-x2+x3+1-x+x2)-(x+x2+x3-1-x-x2)(1+x2+x)(1+x2-x)
=(x3+1)-(x3-1)(1+x2)2-x2
=(x3+1)-(x3-1)1+2x2+x4-x2
=x3+1-x3+1x4+x2+1
=2x4+x2+1
উত্তর :2x4+x2+1
ঘ. a2+16b2a2-16b2-a-4ba+4b
=a2+16b2a2-16b2-a-4ba+4b
=a2+16b2(a+4b)(a-4b)-a-4ba+4b
=a2+16b2-(a-4b)2(a+4b)(a-4b)
=a2+16b2-(a2-2.a.4b+16b2)(a+4b)(a-4b)
=a2+16b2-(a2-8ab+16b2)(a+4b)(a-4b)
=a2+16b2-a2+8ab-16b2a2-(4b)2
=8aba2-16b2
উত্তর: 8aba2-16b2
ঙ. 1x-y-x2-xy+y2x3+y3
=(x3+y3)-(x-y)(x2-xy+y2)(x-y)(x3+y3)
=x3+y3-(x3-x2y+xy2-x2y+xy2-y3)(x-y)(x3+y3)
=x3+y3-x3+x2y-xy2+x2y-xy2+y3(x-y)(x3+y3)
=2x2y-2xy2+2y3(x-y)(x3+y3)
=2y(x2-xy+y2)(x-y)(x+y)(x2-xy+y2)
=2yx2-y2
উত্তর :2yx2-y2